Upaya Penurunan Nyeri Pasien Post Open Reduction Internal Fixation Fraktur Ankle Dextra - Indriyaswari, Dina Septiyani, Okti Sri Purwanti, S.Kep, Ns, M.Kep .,Ns SP.Kep. MB (2017)
The number of traffic accidents in Indonesia from year to year is increasing, one contributing factor is human error factor. Traffic accidents can cause ankle fractures. To deal with ankle fracture ORIF(Open Reduction Internal Fixation) needed to be done to stabilize the spine using plate, screw and metal pins. The problem that often appears in patients of post ORIF is pain. Pain occurs due to disconnection of bone that causes damage to muscles and skin. The focus of the nurse in this case is to treat pain complained of by the patient. This study aims to provide nursing care to patients in pain reduction post ORIF with the assessment, formulate diagnoses, nursing interventions, do the implementation, and evaluate the taken action. The author uses descriptive method through a case study approach in the Intensive Care Unit (ICU). In obtaining the data, the authors used several ways including through medical records, interviews, observation, physical examination, and journals documentation and books. The results obtained after nursing care for 3 x 24 hour is nursing problem was resolved. It can be concluded that deep breath relaxation techniques proven effective to reduce postoperative pain patients ORIFankle fracture. This technique can be done anytime and good because it does not have side effects. The author suggested actions in the breath relaxation techniques can be applied as an independent nursing actions to reduce pain in hospital patients